Health information behaviour of undergraduate students in Information Studies and Physiotherapy: a comparative survey - Efthymiou, Foteini; Kyprianos, Konstantinos; Koulouris, Alexandros; Marketou, Asimina; Kapllani, Florinda; Triantafyllou, Ioannis (Journal of Integrated Information Management, 2024)
Purpose – This survey investigated the health information behaviour of undergraduate students at the University of West Attica. In particular, the survey took place among students of the Department of Archival, Library and Information Studies, where information literacy is taught and in the Department of Physiotherapy, where health subjects are taught. The aim was to discover if any or if both of the above target groups have adopted efficient health information behaviour. Design/methodology/approach – The survey investigated the following: the preferred formats of health information sources and the preferred search techniques of the two target groups; their preferred health information sources and the criteria they use to evaluate and trust a health-related source; the main criterion the participants use to evaluate the content of health information sources; and their perception of the term "information literacy". The methodological approach used was a mainly quantitative online survey administered to a sample from the two aforementioned target groups, within a limited time frame, in the winter of 2022. Findings - Physiotherapy students seem less adequately information literate than Archival, Library and Information Studies students. Originality/value – The findings of this comparative survey are unique in the Hellenic academic environment and lead to the suggestion that information literacy skills should be taught to every Department of the University.